(untitled) (Research, Society and Development, 2022)
Considering that COVID-19 is a respiratory disease transmitted by contact and places of incarceration are an environment that imposes additional risks for viral spread, this study sought to identify cases of SARS-CoV-2 infection in socio-educational units. We evaluated the seroprevalence of IgM and IgG for SARS-CoV-2 in workers and adolescents confined in five socio-educational units. Adolescents and workers tested positive for IgM (n=8, each), IgG (n=26; n=6) and both (n=13; n=6), with a greater chance of detecting IgG (OR: 2.16, p = 0.03) and both (OR: 68.59, p <0.0001) in adolescents who lived in shared accommodation accommodation (unit 5) than those who lived in separate rooms (units 1-4). The study showed the prevalence of COVID-19 in a socio-educational community, where the type of housing occupied by the individuals (single rooms vs a dormitory) was the main determining factor or the spread of the disease. Even adolescents in confinement presented antibodies to SARS-CoV-2.